Handbook in the History of Philosophy. - "Avey, Albert E." (New York, 1958)
Featuring contributions by distinguished scholars from ten countries, The Wiley Handbook of the History and Philosophy of Criminology provides students, scholars, and criminologists with a truly a global perspective on the theory and practice of criminology throughout the centuries and around the world. In addition to chapters devoted to the key ideas, thinkers, and moments in the intellectual and philosophical history of criminology, it features in-depth coverage of the organizational structure of criminology as an academic discipline world-wide.
Keywords: Philosophy